PENERAPAN METODE DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD NEGERI 095 GUNUNGTUA - Agus Salim; Rahmi Seri Hanida; Ali Yusron (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study aims to assess the improvement in students' learning outcomes in science lessons focused on energy sources and energy transformation. The research uses a classroom action research (CAR) approach with the objective of enhancing students' academic performance. The study participants are fourth-grade students from SD Negeri 095 Gunung Tua in Panyabungan Subdistrict, comprising 17 students in total. Data collection methods include observation, tests, and documentation. Results indicate that student learning outcomes improved from an average score of 66.18 in the first cycle—where 7 students (29.41%) met the minimum competency criteria (KKM) and 12 students (70.59%) did not—to an average score of 81.65 in the second cycle, with 15 students (88.23%) achieving the KKM and only 2 students (11.76%) falling short, marking a average 17.64% increase. These findings suggest that using the Discovery Learning method in fourth-grade science lessons on energy sources and energy transformation at SD Negeri 095 Gunung Tua has effectively enhanced student learning outcomes.